The Impact of Learning Management System “arabi.id” Web-Based Application on Developing ArabicLanguage Skills - Moh Ismail; Fairuz Subakir Ahmad; Muhammad Alamuddin Ma'ruf (Universitas Islam Negeri Palangka Raya, 2023)
Until recently, few educational institutions have developed and integrated Arabic language learning curricula with LMS. This study aims to develop a proposed Learning Management System (LMS) program designed to enhance the Arabic proficiency of non-native speakers. It investigates the impact of this program on cognitive fulfilment and language advancement among non-native Arabic learners at the University of Darussalam Gontor, Indonesia. The researcher utilized a quasi-experimental and descriptive research approach, deemed most suitable for this study's nature. Data collection involved 80 students from the University of Darussalam Gontor, employing various tools such as tests, questionnaires, interviews, and observation. The study yielded significant outcomes, including creating the proposed LMS, arabi.id. After completing the research, statistically significant improvements were observed in the experimental and control groups' listening, speaking, reading, and writing abilities, with a more substantial positive impact on the experimental group. Moreover, the experimental group's pretest and post-test results showed statistically significant differences in proficiency levels (listening, speaking, reading, and writing). The study's findings suggest that non-native Arabic speakers can benefit from e-learning courses to enhance their language skills. Recommendations include implementing LMS-based Arabic instruction, encouraging instructors to integrate LMS into the Arabic teaching curriculum, and increasing the availability of Arabic educational websites.